5問 足し算 分数足し算 数学・算数の教材公開ページ

20 

Loading....

Loading....

Loading....

Loading....

Loading....

全文

(1)

(1) 21 4 + 4

1

2 = (2) 2

5 6 + 6

1 3 =

(3) 25 6 + 4

2

3 = (4) 2

1 3 + 5

5 6 =

(5) 34 5 + 5

3 4 =

(2)

(1) 21 4 + 4

1

2 =

6

3

4

(2) 2

5 6 + 6

1

3 =

9

1

6

(3) 25 6 + 4

2

3 =

7

1

2

(4) 2

1 3 + 5

5

6 =

8

1

6

(5) 34 5 + 5

3

4 =

9

11

20

(3)

(1) 2 5 + 3

1

4 = (2) 1

2 3 +

5 6 =

(3) 11 5 +

1

4 = (4)

1 5 + 1

2 3 =

(5) 31 6 + 2

1 4 =

(4)

(1) 25 + 3 1 4 =

3

13

20

(2) 1

2 3 +

5

6 =

2

1

2

(3) 11 5 +

1 4 =

1

9

20

(4)

1 5 + 1

2

3 =

1

13

15

(5) 31 6 + 2

1

4 =

5

5

12

(5)

(1) 11 3 + 3

1

6 = (2) 4

2 3 + 1

5 6 =

(3) 32 3 + 1

1

6 = (4) 2

1 3 + 1

5 6 =

(5) 21 3 + 2

5 6 =

(6)

(1) 11 3 + 3

1

6 =

4

1

2

(2) 4

2 3 + 1

5

6 =

6

1

2

(3) 32 3 + 1

1

6 =

4

5

6

(4) 2

1 3 + 1

5

6 =

4

1

6

(5) 21 3 + 2

5

6 =

5

1

6

(7)

(1) 13 5 +

1

2 = (2) 2

1 4 + 3

1 2 =

(3) 11 2 +

3

4 = (4) 3

5 6 + 2

1 4 =

(5) 25 6 +

2 3 =

(8)

(1) 13 5 +

1 2 =

2

1

10

(2) 2

1 4 + 3

1

2 =

5

3

4

(3) 11 2 +

3 4 =

2

1

4

(4) 3

5 6 + 2

1

4 =

6

1

12

(5) 25 6 +

2 3 =

3

1

2

(9)

(1) 1 2 + 2

4

5 = (2) 3

5 6 + 2

1 3 =

(3) 15 6 + 5

1

3 = (4) 2

1 2 + 1

1 5 =

(5) 41 6 + 3

3 4 =

(10)

(1) 12 + 2 4 5 =

3

3

10

(2) 3

5 6 + 2

1

3 =

6

1

6

(3) 15 6 + 5

1

3 =

7

1

6

(4) 2

1 2 + 1

1

5 =

3

7

10

(5) 41 6 + 3

3

4 =

7

11

12

(11)

(1) 31 2 + 1

1

3 = (2) 1

5 6 + 4

1 3 =

(3) 12 3 + 4

1

2 = (4)

1 2 + 4

2 3 =

(5) 31 6 + 4

2 3 =

(12)

(1) 31 2 + 1

1

3 =

4

5

6

(2) 1

5 6 + 4

1

3 =

6

1

6

(3) 12 3 + 4

1

2 =

6

1

6

(4)

1 2 + 4

2

3 =

5

1

6

(5) 31 6 + 4

2

3 =

7

5

6

(13)

(1) 2 5 + 2

3

4 = (2) 1

5 6 + 1

1 3 =

(3) 11 3 + 2

5

6 = (4) 3

1 3 + 4

5 6 =

(5) 11 4 + 2

2 3 =

(14)

(1) 25 + 2 3 4 =

3

3

20

(2) 1

5 6 + 1

1

3 =

3

1

6

(3) 11 3 + 2

5

6 =

4

1

6

(4) 3

1 3 + 4

5

6 =

8

1

6

(5) 11 4 + 2

2

3 =

3

11

12

(15)

(1) 25 6 + 1

2

3 = (2)

1 2 + 1

3 4 =

(3) 11 6 + 4

1

2 = (4) 1

3 5 +

1 2 =

(5) 53 4 + 1

4 5 =

(16)

(1) 25 6 + 1

2

3 =

4

1

2

(2)

1 2 + 1

3

4 =

2

1

4

(3) 11 6 + 4

1

2 =

5

2

3

(4) 1

3 5 +

1

2 =

2

1

10

(5) 53 4 + 1

4

5 =

7

11

20

(17)

(1) 11 4 + 3

1

2 = (2) 2

3 5 + 4

1 2 =

(3) 15 6 + 1

2

3 = (4) 3

5 6 + 4

2 3 =

(5) 11 3 + 1

5 6 =

(18)

(1) 11 4 + 3

1

2 =

4

3

4

(2) 2

3 5 + 4

1

2 =

7

1

10

(3) 15 6 + 1

2

3 =

3

1

2

(4) 3

5 6 + 4

2

3 =

8

1

2

(5) 11 3 + 1

5

6 =

3

1

6

(19)

(1) 1 6 + 2

1

2 = (2) 4

1 2 + 4

3 4 =

(3) 25 6 + 1

3

4 = (4) 2

5 6 + 2

2 3 =

(5) 22 3 +

5 6 =

(20)

(1) 16 + 2 1 2 =

2

2

3

(2) 4

1 2 + 4

3

4 =

9

1

4

(3) 25 6 + 1

3

4 =

4

7

12

(4) 2

5 6 + 2

2

3 =

5

1

2

(5) 22 3 +

5 6 =

3

1

2

Updating...

参照

Updating...

関連した話題 :